The Opposition between Good and Evil in the Story of Jamshid - Ya’aghoubi Ghazvini, Fatemeh (2020)
The good-evil opposition is amongst the most pivotal themes of Shahnameh. Belief in two evil and good forces has found its way from the heart of the ancient Iranian myths into Shahnameh making this epical work the arena of the battle between the good and evil forces. In this eternal battle which is as old as the mankind history, the symbols of good rise up against the manifestations of evil and each of them try overcoming the other. Kingship of Jamshid can be divided into two different sections. In the first period, he invents a lot of things based on his enjoyment of the divine glory and gives rise to a golden period for the Iranians through his services. In this period, the good forces have domination over the evil forces and Jamshid symbolizes the good. His interventions are in line with endowing comfort and tranquility to Urmazd’s creatures. In the second period, Jam thinks of himself as the God and starts exercising ingratitude, untruthfulness and insanity and becomes the symbol of evildoing and loses the divine glory and sets the ground for his own wastage and this makes the Iranians resort to Zahhak.